GLP-1 and GLP-1/GIP Incretin Agonists and Related Therapies in Metabolic Obesity: A Narrative Review of Pivotal Trials, Pathophysiological Foundations, and Practical Management of Complications - Belmontes - Gutiérrez , D.A.,; Jaramillo - Santos , J.,; Isais – Moreno , D.M;; Hernández - Aguirre , U.G.,; Pérez – Silva , I.A (Revista de Ciencias Médicas Torreón, 2026)
The rapid adoption of glucagon-like peptide-1 receptor agonists, GLP-1/glucose-dependent insulinotropic polypeptide coagonists and related incretin-based therapies has reshaped the management of obesity, type 2 diabetes and cardiometabolic complications. Nevertheless, widespread use outside appropriate medical settings has raised concerns about prescribing by untrained personnel, non-regulated magnitud absoluta del efecto, eventos adversos y products, inadequate titration and insufficient gastrointestinal, renal, nutritional and glycemic follow-up. This narrative review summarizes the pivotal trials and major real-world evidence supporting current prescriptions of liraglutide, dulaglutide, semaglutide, tirzepatide and emerging therapies. A standardized clinical framework is used across studies: population, intervention, comparator, primary endpoint, absolute effect size, safety and applicability. The review also expands the mechanistic rationale by which weight loss and potentially weight- independent pharmacologic actions may influence cardiovascular disease, heart failure with preserved ejection fraction, chronic kidney disease, obstructive sleep apnea, osteoarthritis, polycystic ovary syndrome and metabolic dysfunction-associated steatotic liver disease. Practical recommendations are provided for hypoglycemia prevention, dehydration, acute kidney injury, lean mass preservation and gastrointestinal adverse event management, including insulin/sulfonylurea adjustment, hydration, protein prescription and resistance training.